Retorica e politica nel Risorgimento: la Repubblica romana del 1849 - Silvia Tatti (Laboratoire Italien)
The essay aims to illustrate how a revolutionary rhetoric was built in the years 1848-49. Poetry continues the tradition of political and civil language of the late eighteenth century - early nineteenth, but revolutionary events, even the Roman Republic of 1849, push to a greater attention to the popularity.